2010
DOI: 10.1097/olq.0b013e3181b6f284
|View full text |Cite
|
Sign up to set email alerts
|

The Danish PEP Registry: Experience With the Use of Postexposure Prophylaxis (PEP) Following Sexual Exposure to HIV From 1998 to 2006

Abstract: This nationwide study showed a steady but moderate increase in the use of PEP after sexual HIV-exposure from 1998 to 2006. Time to initiation of PEP was low and the PEP prescription practice was targeted toward high risk exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
0
24
0
4
Order By: Relevance
“…Study settings included sexual assault services4 7 15 20–22 25 28 29 34 35 and hospital emergency departments 3 8 37–39. In three studies, data were obtained from PEP databases and sexual assault was studied as a subgroup of ‘sexual exposure’ or ‘non-occupational exposure’ 26 27 30. Eight studies were conducted in developing countries 4 24 25 32–36.…”
Section: Resultsmentioning
confidence: 99%
“…Study settings included sexual assault services4 7 15 20–22 25 28 29 34 35 and hospital emergency departments 3 8 37–39. In three studies, data were obtained from PEP databases and sexual assault was studied as a subgroup of ‘sexual exposure’ or ‘non-occupational exposure’ 26 27 30. Eight studies were conducted in developing countries 4 24 25 32–36.…”
Section: Resultsmentioning
confidence: 99%
“…This, of course, leaves aside those studies that focus on individuals actively seeking nPEP [8][9][10][11], who obviously know of its existence.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have attempted to characterize the types of person requesting nPEP at health care facilities [8][9][10][11]. Other studies have examined the knowledge that potential users have of its existence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of New York State Emergency Department physicians in 2006 further indicated that a lack of resources and physician education were associated with low rates of provision of NPEP [8]. There are no recent longitudinal reports of trends in NPEP use in the United States, though other settings have been observing a rise in NPEP utilization over time [912]. …”
Section: Introductionmentioning
confidence: 99%